T-singularidade: dinâmica, estabilidade e teoria de controle - Cespedes, Oscar Alexander Ramírez (2013)
Consider a nonsmooth vector fields in R3 defined by parts on a smooth manifold of dimension one, such that it is tangent to both sides simultaneously, in fold points, visibles or invisibles. In this paper we study a local dynamics of the singularity type two-fold invisible-invisible known as Teixeira singularity, revealing new scenes of bifurcations and the nonlinear effects around the bifurcation already known, determining conditions for the existence of invariant sets (limit cycles) and the possible existence of a set with a nondeterministic chaos. Furthermore, we discuss the occurrence of this singularity in switched feedback control systems and some numerical simulations are presented.